Ways to improve the social efficiency of small and medium-sized businesses in the context of digitalization - A. V. Denikin; Z. D. Denikina; N. V. Kubikova (Цифровая социология, 2023)
This article discusses the issue related to ways to improve the social efficiency of small and medium-sized businesses in the context of digitalization. The authors consider key aspects concerning the internal component of business processes through the prism of a behaviorist approach – study the role of human capital in the formation of social efficiency of the company, identify ways of measuring it and the role of job satisfaction, as well as the impact of this indicator on the productivity of the workforce as a whole. The social efficiency of a company is a complex phenomenon, therefore, the study of ways to improve it through internal business processes is important. As the main conclusions to the work, the authors formulate recommendations for improving the level of job satisfaction through the integration of the latest digital technologies. An important place in this article is devoted to the study of the issue related to the factors of increasing job satisfaction. The authors consider the main groups of factors that form the level of employee satisfaction with work. Based on the identified factors, the authors make recommendations to improve the social efficiency of the company. In the final part of the article, the authors make conclusions regarding the further development of the social efficiency of small and medium-sized businesses in the conditions of digitalization.